Cancer Risk in Patients With Autoimmune Hepatitis: A Nationwide Population-Based Cohort Study With Histopathology. Issue 2 (29th April 2021) - Sharma, Rajani; Verna, Elizabeth C; Simon, Tracey G; Söderling, Jonas; Hagström, Hannes; Green, Peter H R; Ludvigsson, Jonas F
Abstract: We aimed to determine the risk of incident cancer in autoimmune hepatitis (AIH) compared with the general population and siblings. AIH was defined by the presence of a medical diagnosis of AIH and results of examination of a liver biopsy specimen in a nationwide Swedish population-based cohort study. We identified 5, 268 adults with AIH diagnosed during 1969–2016 and 22, 996 matched, general population, reference individuals and 4, 170 sibling comparators. Using Cox regression, hazard ratios were determined for any incident cancer, and subtypes were determined from the Swedish Cancer Register. During follow-up, a cancer diagnosis was made in 1, 119 individuals with AIH (17.2 per 1, 000 person-years) and 4, 450 reference individuals (12.0 per 1, 000 person-years). This corresponded to a hazard ratio of 1.53 (95% confidence interval: 1.42, 1.66). Cancer risk was highest in those with cirrhosis. There was a 29.18-fold increased risk of hepatocellular carcinoma (HCC) (95% confidence interval: 17.52, 48.61). The annual incidence risk of HCC in individuals with AIH who had cirrhosis was 1.1% per year. AIH was also linked to nonmelanoma skin cancer (hazard ratio (HR) = 2.69) and lymphoma (HR = 1.89). Sibling analyses yielded similar risk estimates for any cancer (HR = 1.84) and HCC (HR = 23.10). AIH is associated with an increased risk of any cancer, in particular, HCC and extrahepatic malignancies. The highest risk for cancer, especially HCC, is in patients with cirrhosis.